Telomerase Reverse Transcriptase (TERT) Expression, Telomerase Activity, and Expression of Matrix Metalloproteinases (MMP)-1/-2/-9 in Feline Oral Squamous Cell Carcinoma Cell Lines Associated With Felis catus Papillomavirus Type-2 Infection - Altamura, Gennaro; Martano, Manuela; Licenziato, Luca; Maiolino, Paola; Borzacchiello, Giuseppe (Frontiers in Veterinary Science, 2020)
Telomerase activity contibutes to cell immortalization by avoiding telomere shortening at each cell division, indeed its catalytic subunit telomerase reverse transcriptase (TERT) is over-expressed in many tumors, including human oral squamous cell carcinoma (hOSCC). In these tumors, matrix metalloproteinases (MMPs), a group of zinc-dependent endopeptidases involved in cell migration, contribute to invasive potential of cancer cells. A proportion of hOSCC is associated with infection by high-risk human papillomavirus (HR-HPVs), whose E6 oncogene enhances TERT and MMPs expression, thus promoting cancer progression. Feline oral squamous cell carcinoma (FOSCC) is a malignant tumor with highly invasive phenotype, however studies on telomerase activity, TERT and MMPs expression are scarce. In this study, we demonstrate telomerase activity, expression of TERT and its transcriptional activator cMyc along with expression of MMP-1, -2 and -9 in FOSCC derived cell lines SCCF2 and SCCF3, suggesting a contribution by these pathways in cell immortalization and invasion in these tumors. Recent studies suggest that a sub-group of FOSCC as well as SCCF2 and SCCF3 are associated with Felis catus PV type-2 (FcaPV-2) infection. However, in this work FcaPV-2 E6 gene knock-down caused no shift in either TERT, cMyc or MMPs levels, suggesting that, unlike human counterpart, the viral oncogene plays no role in their regulation.